INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PERUSAHAAN; SUATU ANALISIS DENGAN PENDEKATAN PARTIAL LEAST SQUARES - Ervina, Maya; Abdurahim, Ahim; Suryanto, Rudy (Journal of Accounting and Investment, 2008)
This research aims to know the relationship between intellectual capital components (human capital, structural capital, and customer capital) with company’s performance and manufacture industry in Indonesia. This study examines 50 companies that listed in Indonesian Capital Market Directory from 2003 until 2007 the financial report that published every years. The result show that there is significant positive relations amng intellectual capital with company’s performance. But the result not support relationship between intellectual capital with future company’s performance and future company’s performance with rate of growth of intellectual capital (ROGIC).